2021
DOI: 10.1182/blood.2020009895
|View full text |Cite
|
Sign up to set email alerts
|

Toward prevention of childhood ALL by early-life immune training

Abstract: B-cell precursor acute lymphoblastic leukemia (BCP-ALL) is the most common form of childhood cancer. Chemotherapy is associated with life-long health sequelae and fails in approximately 20% of cases. Thus, prevention of leukemia would be preferable to treatment. Childhood leukemia frequently starts before birth, during fetal hematopoiesis. A first genetic hit (e.g. the ETV6-RUNX1 gene fusion) leads to the expansion of pre-leukemic B-cell clones, which are detectable in healthy newborn cord blood (up to 5%). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(81 citation statements)
references
References 168 publications
(99 reference statements)
4
71
0
Order By: Relevance
“…Both hypotheses propose that ALL is a consequence of an abnormal response to common infections. Currently, three additional models of ALL evolution exist, which also point to infection-induced immune disturbances as being responsible for leukemia evolution as recently summarized by Hauer et al (65). A more detailed view into the role of infections is given elsewhere (17, 66, 67).…”
Section: Environmental Risk Factors Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both hypotheses propose that ALL is a consequence of an abnormal response to common infections. Currently, three additional models of ALL evolution exist, which also point to infection-induced immune disturbances as being responsible for leukemia evolution as recently summarized by Hauer et al (65). A more detailed view into the role of infections is given elsewhere (17, 66, 67).…”
Section: Environmental Risk Factors Infectionsmentioning
confidence: 99%
“…The observation that predisposed mice with a depleted gut microbiota developed leukemia, even without infectious stimuli, suggests that an intact gut microbiome protects genetically predisposed mice from developing pB-ALL (82). This protective effect is likely mediated through the release of microbial components or metabolites, or direct microbial binding to Toll-like receptors on innate immune cells (65,67).…”
Section: Experimental Evidence For An Infection-mediated Childhood Leukemogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial composition is well adjusted to the specific conditions in different areas of the human body, depending on age, environmental lifestyle, antibiotic therapy, and diet. The symbiotic interplay between host and bacteria results in a healthy mucosa, which offers protection from overt pathogens and provides nutrients, such as short fatty acids and branched-chain amino acids, as well as the production of glycans and lactic acids (Table 1) [14][15][16][17][18][19][20]. Furthermore, the microbiome shapes and influences the immune system in a positive way by inducing innate and adaptive immune responses [4].…”
Section: Current Status Of Microbiome Analysis In Pediatric Allmentioning
confidence: 99%
“…Furthermore, the microbiome shapes and influences the immune system in a positive way by inducing innate and adaptive immune responses [4]. Studies have further revealed a profound impact on the early development of the innate immune system, referred to as trained immunity [15].…”
Section: Current Status Of Microbiome Analysis In Pediatric Allmentioning
confidence: 99%